2020
DOI: 10.1111/hepr.13492
|View full text |Cite
|
Sign up to set email alerts
|

Calculated body muscle mass as a useful screening marker for low skeletal muscle mass and sarcopenia in chronic liver disease

Abstract: Aim Sarcopenia is a harmful condition in patients with chronic liver disease. However, the evaluation of body muscle mass requires expensive instrumentation. The sarcopenia index (SI): (creatinine / cystatin C × 100) has been reported to correlate with muscle volume. A calculated body muscle mass (CBMM) using creatinine, cystatin C, and bodyweight also correlates with muscle mass. We evaluated the applicability of using SIs and CBMMs as screening methods for sarcopenia. Methods Patients (n = 303) with liver da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Separately, CBMM appeared to be a suitable screening method for sarcopenia based on the results of the present study. In our previous study, it was shown that the AUC for CBMM against sarcopenia was 0.78504 in females and 0.85067 in males (9), in agreement with the results of the present study. Since the study population was different between the previous and present study, the efficacy of CBMM for sarcopenia screening has been validated by both.…”
Section: Male Female ------------------------------------------------supporting
confidence: 93%
See 3 more Smart Citations
“…Separately, CBMM appeared to be a suitable screening method for sarcopenia based on the results of the present study. In our previous study, it was shown that the AUC for CBMM against sarcopenia was 0.78504 in females and 0.85067 in males (9), in agreement with the results of the present study. Since the study population was different between the previous and present study, the efficacy of CBMM for sarcopenia screening has been validated by both.…”
Section: Male Female ------------------------------------------------supporting
confidence: 93%
“…In the present study, sex and age also affected the rate of sarcopenia, and a difference between the sexes was also found in our previous study as well (9). Age is a well-established factor for sarcopenia (29).…”
Section: Male Female ------------------------------------------------supporting
confidence: 89%
See 2 more Smart Citations
“…The presence of RLS was defined by the RLS criteria. We previously reported that the receiver operating characteristic (ROC) curve analysis between sarcopenia and CBMM revealed an area under the ROC curve of 0.78504 in women and 0.86067 in men, and the cut-off CBMM values for sarcopenia were 27.903 in women and 39.731 in men with chronic liver disease ( 28 ). The sex, HCV genotype, DAAs, age (<65 years old), minimal hepatic encephalopathy (MHE; 22 cases), poor sleeper according to the ESS (4 cases), RLS (13 cases), psychological distress (PD) in K-6 (2 cases), and sarcopenia in CBMM (women, <28; men, <40; 70 cases) were not significantly associated with the dGHN.…”
Section: Resultsmentioning
confidence: 99%